Fabrication and characterization of silicon-based Ba0.7Sr 0.3TiO3 thin films for FeFET applications - Saif, Ala'eddin A. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Link to publisher's homepage at http://ieeexplore.ieee.org